Power struggles : dignity, value, and the renewable energy frontier in Spain - Franquesa, Jaume (New anthropologies of Europe., 2018)
Wind energy is often portrayed as a panacea for the environmental and political ills brought on by an overreliance on fossil fuels, but this characterization may ignore the impact wind farms have on the regions that host them. Power Struggles investigates the uneven allocation of risks and benefits in the relationship between the regionsthat produce this energy and thosethat consume it. Jaume Franquesa considers Spain, a country where wind now constitutes the main source of energy production. In particular, he looks at the Southern Catalonia region, which has traditionally been a source of energy production through nuclear reactors, dams, oil refineries, and gas and electrical lines. Despite providing energy that runs the country, the region is still forced to the political and economic periphery as the power they produce is controlled by centralized, international Spanish corporations. Local resistance to wind farm installation in Southern Catalonia relies on the notion of dignity: the ability to live within one's means and according to one's own decisions. Power Struggles shows how, without careful attention, renewable energy production can reinforce patterns of exploitation even as it promises a fair and hopeful future.